Environmental life cycle assessment of desalination : the influence of different life cycle impact assessment methods on the characterization, normalization and weighting results - Ho, Yee-Cheng. (2011)
The main purpose of this work is to examine whether the environmental impacts of reverse osmosis (RO) desalination fluctuates according to different Life Cycle Impact Assessment methods used, and if the aforementioned is valid, then the extent to which such fluctuations occur and the possible impacts of this occurrence. The environmental costs in different impact categories are assessed using a generic LCIA method, CML 2 and an US-specific method – TRACI, applied on an RO desalination plant model in the United States. The input and output flows of the RO plants were based on previous studies. Life Cycle Inventory used was adopted from the Ecoinvent Database with specific US datasets. The results concluded that the choice of LCIA method did have significant influence in the LCA characterization and normalization results of the desalination process. The work also identified the variation in coverage level of different material flows, characterization models used in the method, and differentiation of environmental interventions between two LCIA methods to be the main reasons for disparity in characterization scores for various impact categories – such as acidification, eutrophication, photochemical oxidation, human health, and ecotoxicity potentials. The large discrepancies for normalization scores were attributed to the difference in normalization factors used for computation. This work also recommended some suggestions in choosing the appropriate LCIA method for desalination industry and developing desalination-specialized LCIA method.